(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2012)
n today’s Brazil, it’s hard to think of any issue with major repercussions (social, political or economic) that isn’t discussed by the Judiciary. Whether in cases where the Legislative Branch issues a law regulating the matter or the Executive Branch regulates it, or in cases where such normative acts should have been formulated and were not, it is certain that the Judiciary has become a new arena for debating the most diverse issues. In the first case, it is called upon to correct any illegality or unconstitutionality of the contested normative act; in the other, it is called upon to regulate the issue, at least until the competent body does so. Numerous discussions have guided the debate on judicial action, from those focused on the legitimacy of the body to those centered on the limits of intervention. The central point in any of them is always the principle of the separation of powers. The aim of this paper is to provide a brief overview of judicial control of public policies in Brazil, especially the powers of the judge and the sufficiency of existing legislation.